Treatment of brain aneurysms. - Schonfeld AR; McMullen MA (Radiologic Technology)
Up to 5% of the population may have an intracranial aneurysm, although many of these people are unaware of its presence. Most intracranial aneurysms remain asymptomatic, but a small proportion of them will rupture and bleed, causing life-threatening complications. Once diagnosed, treatment of aneurysms may include surgery or a minimally invasive endovascular coiling technique. As technologies improve and more aneurysms are deemed suitable for endovascular repair, there will be an increasing demand for radiologic technologists or radiologist assistants skilled in these complex diagnostic and therapeutic procedures. This article is a Directed Reading. Your access to Directed Reading quizzes for continuing education credit is determined by your area of interest. For access to other quizzes, go to www.asrt.org/store.